SEKOLAH BAHASA: THE ALTERNATIVE TRAINING FOR BIDIK MISI STUDENTS TO CONTRIBUTE ENGLISH STUDENT’S LECTURE IN IAIN KUDUS - Suciati, Suciati; Nikmah, Alfu (Institut Agama Islam Negeri (IAIN) Kudus, 2017)
AbstractFor developing the students’ capability in English language, IAIN Kudus, especially Ma’had Institute held Sekolah Bahasa for the students who get Bidik Misi scholarship. The objectives of this research were getting information related to the materials given in Sekolah Bahasa program, analyzing the role of the program to the students and analyzing the problems in the program implementation. The research method used in this study was a qualitative descriptive method. Data was collected through observation, interview, questionnaire and document analysis were. The results of the research showed that: 1) the materials of Sekolah Bahasa were TOEFL, grammar, reading, pronunciation, academic writing, speech, translation and debate; 2) Sekolah Bahasa has important and big role to the students’ English capability because they can get the knowledge related to English that they do not have such materials or subjects in the lecture program; and 3) the problems in that program were the big number of the students in the classroom, the lack of students’ motivation, the different students’ background, and teaching/learning method.